Upaya Penderita Hipertensi untuk Mempertahankan Pola Hidup Sehat - Sunarti Sunarti; Imam Sunarno; Alvino Alvino (Journal of Ners and Midwifery, 2015)
Healthy lifestyle is a lifestyle with attention to factors - certain factors that affect health, such as diet and exercise. The purpose of this research is to identify how the efforts of patients hypertension to maintain a healthy lifestyle. Methods this research uses descriptive design. The population in this research were all patients with hypertension in Poly UPTD Kesehatan Kecamatan Sukorejo Blitar total of 220 people, the number of samples in this study were 33 respondents and using purposive sampling technique. Data collection is done by giving questionnaires. Time of data collection was conducted on 20 June 2013 to 02 July 2013. The results showed that for 57.6% (19 respondents) had a good effort, 39.4% (13 respondents) had enough attempts, and 3% (1 respondent) had less effort. Recommendations from this study are expected to continue to provide health services well and provide health education to the public about healthy lifestyle that should be done for patients with hypertension